The effect of electronic job aid assisted one-to-one counselling to support exclusive breastfeeding among 0–5-month-old infants in rural Bangladesh - Billah, Sk Masum; Ferdous, Tarana E.; Siddique, Abu Bakkar; Raynes-Greenow, Camille; Kelly, Patrick; Gillespie, Stuart; Hoddinott, John F.; Menon, Purnima (Wiley, 2022)
Exclusive breastfeeding (EBF) for the first 6 months has established benefits, yet had slow improvements globally. Little is known about electronic job aid-assisted counselling to support EBF. As a secondary outcome of a cluster randomized controlled trial in Bangladesh, we assessed the effect of electronic job aid-supported nutrition counselling and practical demonstration on EBF. We randomized pregnant women to one of five study arms in the trial and followed mother–child dyads until 2 years of age. Community health workers (CHWs) provided breastfeeding counselling with or without prenatal and complementary nutrient supplements in all four intervention arms. The comparison arm continued with the usual practice where mothers could receive nutrition counselling at routine antenatal and postnatal care, and during careseeking for childhood illnesses. We assessed breastfeeding indicators at birth and monthly until the child was 6 months old, in both intervention and comparison arms. To evaluate the effect of nutrition counselling on breastfeeding, we combined all four intervention arms and compared them with the comparison arm. Intervention newborns had half the risk (relative risk [RR]: 0.54, 95% confidence interval [CI]: 0.39, 0.76) of receiving prelacteal feeds than those in the comparison arm. EBF declined steeply in the comparison arm after 3 months of age. EBF was 16% higher in the intervention than the comparison arm at 4 months (RR: 1.16, 95% CI: 1.08, 1.23) and 22% higher at 5 months of age (RR: 1.22, 95% CI: 1.12, 1.33). Maternal background and household characteristics did not modify the intervention effect, and we observed no difference in EBF among caesarean versus vaginal births. Breastfeeding counselling and practical demonstration using an electronic job aid by CHWs are promising interventions to improve EBF and are scalable into existing community-based programmes.